Investigation of piles behavior under lateral cyclic loading - Liu, Chunhui (Array, 2019)
In this paper, the capability of 3D nonlinear finite element models is validated by single pile and 5x3 pile group filed experiments that is subjected to cyclic lateral loading. Then, a series 3D finite elements models are built to analyze the effect of the number of cycles of lateral loading, pile spacing, and pile group arrangement. The results have shown that the number of cycles affected the pile-soil system stiffness seriously, and the pile group effect became insignificant as the increase of pile spacing, while this effect became more significant with the increase of the pile group arrangement. In practical engineering, the pile spacing and pile group arrangement should be considered and chosen carefully.